解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:43:17
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)(y-3
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)
(y-3y+2)(y+3y-2)=[y^ 2-(3y-2)](y^ 2+3y-2)=y^ 4-(3y-2)^ 2=y^ 2(y^ 2-9) 化简得12y-4=0,解得y=1/3
解方程:(y-3y+2)(y+3y-2)=y(y+3)(y-3)
解(y-3分之2y+y+3分之y)×y分之y²-9
解方程3y+1/y+2+2/2-y=3-(3y/y的平方-4)
解方程y-[3y-1]等于5【y+2]
解方程3y(y-1)=2(1-y)
解方程3y^2-(2y+1)(y-2)=(y-5)(y-1)
解方程:3y^2-(2y+1)(y-1)=(y-5)(y+1)
解方程:3y²-(2y+1)(y-2)=(y-5)(y+1)
方程5y(2y-3)=(y+2)(y-2)-1
解分式方程(y+3)/(y^2+y)-1/(1-y)=4/y要过程
解方程:3分之1-y-y=3-2分之y+2(3分之1-y)-y-=3-(2分之y+2)
4(2y+3)=8(1-y)-5(y-2)解方程
解方程:3(y²-6)=(y+2)²+(y-2)²
解方程 2分之3y(y-3分之8)=3y-4
解方程3y(y-1)=2(y-1)
解方程:2y-3[y-4(1-2y)-5]=10
解方程:y(y-2)=3y²-1 ,要布奏的.
解方程(y-3)^3-(y+3)^3=9y(1-2y)